A new low-cost motion control educational equipment - Montesinos-Miracle, Daniel; Galceran-Arellano, Samuel; Gomis-Bellmunt, Oriol; Sudria-Andreu, Antoni (2007 European Conference on Power Electronics and Applications, 2007)
This paper describes a laboratory test bed for motion control. There has been an increasing use of modern digital signal processors (DSPs) in industrial control and other applications in the past few years. Therefore, there is a growing need in industry for engineers who can perform control design and system integration for various applications in motor control. Nowadays educational DSP and control tools are focused on telecommunications, sound and image encoding and decoding. But there is a lack of educational tools for motor control applications. The new low-cos tool presented in this paper includes all the necessary hardware and software tools to implement DSP control algorithms of any type of motor or power converter.